HUBUNGAN KEMATANGAN EMOSI DAN INTERAKSI SOSIAL DENGAN PENYESUAIAN DIRI SISWA MTSN KABANJAHE KABUPATEN KARO - Zulfadli Lingga (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This research aims to know the relation between the maturity of emotion and social interaction with the adaptability of students MTs Country Kabanjahe. The subject of research as many as 75 people. There are three hypothesis proposed in this study: (1) there is a positive relationship between maturity of emotion with the adjustments themselves, (2) there is a posistif relationship between the interaction with social conformity, (3), there is a positive relationship between the maturity of emotions, social interaction with the adjustments themselves. Based on the results of the study found a significant relationship between maturity of emotion with the self adjustment. (r of 0.712 and P 0.05). Determinant of the coefficientsof 50.6% adjustment means 0.506 themselves influenced by emotional maturity. Furthermore, there is a significant relationship between social interactions with self adjustment. (r = 0.619 and P 0.000). Determinant of the coefficientsof 0.383 means that 38.3% adaptability are influenced by social interaction.When a variable maturity together emotion and social interaction there is a significant relationship with self adjustment. This can be seen in the table model summary koefesien where r = 0.719 and P < 0.000. Together the variables X 1 and X 2 affects the variable Y. Determinant of the coefficientsof 0.503 50.3%, meaning that the adjustments themselves are influenced by social interaction and emotional maturity. Whereas 49.7% are influenced by factors other factors that cannot be described in the regression equation (residual).